2017 AIChE Spring Meeting & 13th Global Congress on Process Safety : 6th Process Safety Management Mentoring (PSMM) Forum (Center for Chemical Process Safety/AIChE, 2017)
The Process Safety Management Mentoring (PSMM) Symposium is a tutorial-based track aimed at professionals new to the workforce, new to the field of process safety, and to those simply interested in strengthening their knowledge of process safety. The framework for the track is grounded in the 20 elements of the CCPS's risk-based process safety approach (aka "RBPS").
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books